(untitled) (Bombay Hospital Journal, 2022)
Abstract: Advances in molecular methods has made genetic testing as an imperative parameter, to be used in research studies and clinical practice. The present article includes the evolution of Molecular Diagnostic techniques over a period of two decades leading to the corresponding expansion in identification & classification of various Neuromuscular disorders in the population of mainly Western India. Initially conventional testing was done by mPCR, RFLP-PCR for single gene disorders like DMD/BMD & SMA respectively; followed by MLPA technique, for deletion duplication analysis. Under a research study, immuno-specific Western Blot was used for protein analysis as an initial screening tool for LGMD2B. Sangers sequencing was done for single gene (for a few LGMD2B cases) & known familial variants of LGMD2B & LGMD2A and GNE myopathy. Availability of Next generation sequencing technique involving massive parallel sequencing of multiple genes, improved the possibility of identifying the disease causing/ pathogenic mutations in phenotypically overlapping NMDs like LGMDs and Hereditary Neuropathies. Since last 12 years, over 2,600 patients from mainly western India have been analysed for various neuromuscular disorders. Carrier status of relatives of the probands was also determined in many of the cases. These molecular technologies have enabled to attained definitive diagnosis of different neuromuscular disorders in India. The diagnostic and predictive data generated helps in better management of the disease. It also has immense relevance in carrier and prenatal testing for the families at risk, thereby limiting the occurrence of the diseases in the population.